THE USE OF ICE BREAKING ON THE PROCESS OF WORKSHOP AND ENTERPREUNER LEARNING TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF STUDENT X IS2 CLASS AT SMAN 4 BANDA ACEH - Sri Erlaini Arima; Yuli Heirina Hamid; . Indani (Jurnal Ilmiah Mahasiswa Pendidikan Kesejahteraan Keluarga, 2017)
One of the learning strategies that use to improve motivation and learning outcomes is by using ice breaking. The research that titled The use of Ice breaking on the process of workshop and entrepreneur learning to improve motivation and learning outcomes of student X IS 2 class at SMAN 4 Banda Aceh is aimed to see (1) learning motivation of student with using ice breaking in the workshop and entrepreneur learning process X IS 2 class at SMAN 4 Banda Aceh, 2016/2017 Academic Year amounting to 30 students. The approach taken in this research is quantitative approach, when data obtained, and then processed using statistic method and explained again using words (narration). While the type of research is PTK (Classroom Action Research). The instrument data of data collection are RPP (Lerning Implementation Plan), observation sheet, (observation) teacher and student activity, student worksheet, student motivation sheet on the teaching and learning process with implement ice breaking learning strategy that the learning outcomes analysed using precentage test and student motivation analysed by reference to the criteria of the result of the analyse of the learning motivation. Based on the data analyse can be concluded that: (1)Using Ice breaking on the workshop and entrepreneur learning XIS2 class at SMAN 4 Banda Aceh 2016/2017 Academic Year is increase, it is seen from the results of classical learning completeness from 63,33 % on first sicluss to 86,67% on second sicluss with increased 23,34%. (2) student motivation sheet is increased too from enough category to be good. Average score of motivation obtained on the questionnaire in first sicluss that followed 30 students 64,57% is classified enough. While average score of motivation second sicluss 78,03% is classified good with incerased 13,46%.